2000
DOI: 10.1103/physreve.62.5179
|View full text |Cite
|
Sign up to set email alerts
|

Axial and angular correlations between colloidal particles in narrow cylindrical pores

Abstract: In this work we present a study of the local structure of a model colloidal suspension highly confined inside a cylindrical pore. Such a study is based in Monte Carlo computer simulations, using the repulsive part of the Derjaguin-Landau-Verwey-Overbeek potential as the pair interaction between particles. The structural properties calculated here are the concentration profile n(rho), the axial pair correlation function g(z), and the axial-angular pair correlation function g(z,straight phi). The behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These approaches have made ample use of the standard techniques of the theory of simple liquids: integral equation methods, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] density functional theory ͑DFT͒, [15][16][17][18][19][20][21] and computer simulations. 5,6,8,[10][11][12][22][23][24][25][26][27][28] Besides being applied to the description of the local concentration of a charged colloidal suspension in the vicinity of a flat infinite wall, these techniques have also been successfully employed in the study of the spatial arrangement of colloidal particles confined within closed geometries like planar slits, cylindrical pores, wedgelike regions, square ducts, etc. The distribution of a colloidal suspension near a flat, charged or neutral, wall can be considered as the limiting case of the distribution of colloids in the proximity of a very large, charged or neutral, spherical particle.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have made ample use of the standard techniques of the theory of simple liquids: integral equation methods, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] density functional theory ͑DFT͒, [15][16][17][18][19][20][21] and computer simulations. 5,6,8,[10][11][12][22][23][24][25][26][27][28] Besides being applied to the description of the local concentration of a charged colloidal suspension in the vicinity of a flat infinite wall, these techniques have also been successfully employed in the study of the spatial arrangement of colloidal particles confined within closed geometries like planar slits, cylindrical pores, wedgelike regions, square ducts, etc. The distribution of a colloidal suspension near a flat, charged or neutral, wall can be considered as the limiting case of the distribution of colloids in the proximity of a very large, charged or neutral, spherical particle.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several theoretical studies have found that when small gaseous molecules are confined within these cavities they condense into a wide variety of molecular conformations such as linear arrays, zig-zag configurations, as well as helical and layered structures. [8][9][10] Actually, additional studies on similar related systems have demonstrated that the previous condensed phases and the associated structural transitions as a function of the number of stored molecules seems to be a more general feature of the cylindrical constraint since they have been also observed in colloidal suspensions confined in cylindrical pores, 11 when iodine atoms are encapsulated in SWNT's, 12 as well as for C 60 fullerenes trapped in the inside of carbon nanotubes of different radii. 4 The experimental results discussed in the previous paragraphs have stimulated many theoretical studies of gas adsorption in SWNT's arrays and additional relevant information concerning the role played by geometrical factors such as the nanotube's diameter and the intertube spacing in the sample has been mainly obtained through Monte Carlo simulations 13 and molecular dynamics techniques.…”
Section: Introductionmentioning
confidence: 95%